Impact of hot mix asphalt plant silo storage conditions on blending and diffusion between virgin and RAP binders. Issue 6 (3rd June 2021) - Pirzadeh, Payman; Kadhim, Hawraa; Grant, Daniel L.; Webb, Jonathan D.; Baaj, Hassan; Kriz, Pavel
Abstract : Reclaimed Asphalt Pavement (RAP) is an important component of most Hot Mix Asphalts (HMA). The extent of blending between RAP and virgin binders influences durability and performance of the HMA. The quality of blending also impacts design and manufacturing process of HMA, particularly when RAP content increases. Earlier studies suggested that longer incubation times especially at higher temperatures can increase the extent of blending, predominantly driven by diffusion, between RAP and virgin binders. Storage silos in asphalt plants can be utilised to store HMA at higher temperatures to expedite diffusion between the RAP and virgin binders. This field work expands the scope of previous lab studies on extent of blending and diffusion to plant-produced HMA. Two asphalt plants produced surface (HL-3) and base (HL-8) mixes with different sources and contents of RAP, and two virgin binder grades. HMA silos were sampled at preset time intervals ranging from 0 to 24 h. HMA samples were examined for dynamic moduli and performance properties. Analysis of HMA together with detailed assessment of recovered binders suggest that there is an optimum silo storage time within the range of 8–12 h, during which diffusion approaches completion, yet significant binder aging is not observed. HMA analysis also indicates that resistance to rutting and fatigue cracking can be improved simultaneously for silo-stored samples where diffusion between binders approached completion.